Do practitioners managing mood disorders work to a sub-typing or a 'one size fits all' model?. (February 2013) - Parker, Gordon; Paterson, Amelia; McCraw, Stacey; Friend, Paul; Hong, Michael
Objective: To assess whether psychiatrists in the community operate to a sub-typing model of mood disorders when choosing psychotropic medications. Method: Patients assessed through the Black Dog Institute depression clinic provided information on their previously prescribed and current medications, on how effective they found them and whether they had to be ceased due to side-effects. The prevalence of each medication trialled was analysed according to diagnosis (bipolar I, bipolar II, unipolar melancholic depression or unipolar non-melancholic depression). Results: Analyses indicate that psychiatrists prescribe medications differentially in line with diagnosis. This effect was found in both previously prescribed and currently prescribed medications, and was most distinct for mood stabiliser and antipsychotic medications. Several medications, in contrast, appeared to have been trialled by the majority of patients, regardless of diagnosis. Analyses of effectiveness and cessation due to side-effects were compromised by small sub-sample sizes. Conclusions: Psychiatrists in the community appear to operate to a sub-typing model of mood disorders, preferentially prescribing many medications according to mood disorder sub-type.